Dubai Crisis and Kerala - Sreedevi, V. (Prabandhan: Indian Journal of Management, 2010)
The world is a strange place and becoming stranger day by day. One thing however, is for sure - it’s becoming more globalized, integrated and most importantly, more interdependent. The world is moving towards transnational economy rather than international economy. Transnational economy is the border less economy, characterized by flow of trade and factor of production across national borders , So when the financial system of one country is disturbed, other systems in the country are likely to have proportionate impacts simultaneously. Recent global financial crisis that began like a tiny spark in the US housing finance market in 2007 spread like a wild forest fire that first engulfed the US, then the Western economies and eventually the rest of the world. The crisis impacted the deepest and most wide spread economic meltdown that the world had faced since the great depression.